ADVANCED TWO-PHASE PASSIVE THERMAL CONTROL DEVICES: LOOP HEAT PIPES AND PULSATING HEAT PIPES - Riehl, Roger R. (Revista de Engenharia Térmica, 2006)
This paper presents the development of two-phase passive thermal control devices that can be used at both ground and space applications. These devices operate by acquiring heat through their evaporation section and rejecting through their condensation section, keeping a tight control on the heat source temperature without the presence of moving parts. Recent researches with loop heat pipes (LHPs) have showed the great capability of such a device in managing high levels of heat while keeping the source temperature within certain levels. For this case, experimental tests of a LHP are presented, where the behavior related to its operation with power cycles can be evaluated and its performance can be verified. This paper also presents an investigation of a two-phase thermal control device called pulsating heat pipe (PHP) configured as an open loop. Experimental tests with different working fluids are presented, which shows the great capability of the PHP in operating at both horizontal and vertical orientations and promoting the thermal control, which is highly affected by the working fluid and geometric parameters. The experimental results presented for both devices are intended to contribute for the continuous development of these two passive thermal control devices.